Correlates of changes in children's independent mobility during the COVID-19 pandemic: A Canadian national longitudinal study - Sudipta Roy; Nimesh B. Patel; Mathieu Bélanger; Mariana Brussoni; Guy Faulkner; Katie Gunnell; Mark S. Tremblay; Richard Larouche (Journal of Transport Geography, 2026)

Design and performance of the Low-Energy Module for the Ziré instrument on the NUSES mission: A compact spectrometer for low-energy particles in space high-radiation environments - Muhammd Abdullahi; Roberto Aloisio; Francesco Arneodo; Sindorjon Ashurov; Uygar Atalay; Felicia C.T. Barbato; Roberto Battiston; Mario Bertaina; Elisabetta Bissaldi; Denise Boncioli; Leonid Burmistrov; Franck Cadoux; et al. (Advances in Space Research, 2026)

The tenuous geological record of Precambrian oceanic spreading centers; revisiting the Paleoproterozoic Purtuniq ophiolite sheeted dike complex, Nunavik, Canada - S. Lafrance; C. Guilmette; J.H. Bédard; N. Rayner; G. Mathieu; F. Fournier-Roy (Chemical Geology, 2025)

Expanding Monitoring Capacity for Potential Invasive Species in Arctic Canada With Environmental DNA Metabarcoding - Elizabeth Boyse; Melody S. Clark; Ian M. Carr; Alison J. Cook; Philippe Archambault; Jean E. Holloway; Zhewen Luo; Michael Milton; Mathieu Roy; Jackie Dawson; Victoria L. Peck (Global Change Biology, 2025)
To date, environmental conditions have been enough to act as an effective barrier to prevent non‐indigenous species from arriving and establishing in Arctic Canada. However, rapidly changing climatic conditions are creating more suitable habitats for non‐indigenous species to potentially establish and become invasive. Concurrently, shipping traffic in parts of Arctic Canada has increased by over 250% since 1990, providing an effective vector for transporting non‐indigenous species to the region. Arctic Canada has been historically undersampled, so Arctic biota inventories are incomplete, hampering efforts to establish if a species is new to the region (and potentially invasive) or newly discovered. In this study, we utilize environmental DNA (eDNA) metabarcoding and ships of opportunity to assess eukaryotic community composition and potential invasives along one of the busiest shipping routes, the Northwest Passage. One liter seawater samples were collected in triplicate at 27 locations, targeting touristic hotspots frequently visited by passenger vessels. Eukaryotic DNA was amplified from the 18S rRNA V9 and COI regions, resulting in 126 unique Amplicon Sequence Variants (ASVs) detected with COI and 391 ASVs with 18S, providing an important snapshot of current community composition. Copepods, dinoflagellates, and diatoms were the most abundant taxonomic groups, correlating well with previous net sampler surveys, validating the efficacy of eDNA for biodiversity surveillance. We also report the first detections of a prolific invasive species, the bay barnacle ( Amphibalanus improvisus ), in Arctic Canada. Further work is currently in progress to establish whether these detections represent transient barnacle larvae or sessile adults capable of recruiting and reproducing. Our study demonstrates the utility of eDNA for the detection of non‐indigenous species in a data‐poor area, which, if combined with citizen science initiatives and local communities, could provide a vital monitoring tool for the detection of new invasives in this rapidly changing area.

Corrigendum to “Pre-hispanic wetland irrigation and metallurgy in the South Andean Altiplano (Intersalar Region, Bolivia, XIVth and XVth century CE)” [Quat. Sci. Reviews 338 (2024) 108826] - Stéphane Guédron; Clément Roy; Géraldine Sarret; Julie Tolu; Marie-Pierre Ledru; Sylvain Campillo; Sarah Bureau; Anne-Lise Develle; Charline Guiguet-Covex; Eduardo Queiroz Alves; Mathieu Boudin; Richard Joffre; et al. (Quaternary Science Reviews, 2025)

Pre-hispanic wetland irrigation and metallurgy in the South Andean Altiplano (Intersalar Region, Bolivia, XIVth and XVth century CE) - Stéphane Guédron; Clément Roy; Géraldine Sarret; Julie Tolu; Marie-Pierre Ledru; Sylvain Campillo; Sarah Bureau; Anne-Lise Develle; Charline Guiguet-Covex; Eduardo Queiroz Alves; Mathieu Boudin; Richard Joffre; et al. (Quaternary Science Reviews, 2024)

Parental training with phloroglucinol protects their offspring from biotic and abiotic stressors in Macrobrachium rosenbergii - Suvra Roy; Mathieu Wille; Parisa Norouzitallab; Daisy Vanrompay; Peter Bossier (Aquaculture, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Simulation of the annual and diurnal cycles of rainfall over South Africa by a regional climate model - Benjamin Pohl; Mathieu Rouault; Shouraseni Sen Roy (Climate Dynamics, 2014)

The diurnal cycle of rainfall in South Africa in the austral summer - Mathieu Rouault; Shouraseni Sen Roy; Robert C. Balling (International Journal of Climatology, 2013)
The diurnal cycle of precipitation over South Africa during summer is analysed for the first time using hourly precipitation data from 103 stations for the period 1998–2007. Using harmonic analysis, we found the presence of a distinct diurnal cycle over most of South Africa regarding both the frequency and amount of precipitation events. The standardized amplitudes, indicative of the strength of the diurnal cycle across a region, are strongest over the interior and along the east coast of South Africa with up to 70% explained variance associated with the diurnal cycle. The time of maximum precipitation is late afternoon to early evening in the interior, and midnight to early morning along the Agulhas Current as well as inland in the northeast of the county. The proximity of the warm Agulhas Current plays a role in the diurnal cycle of rainfall at coastal stations. There is an early morning maximum in precipitation in the South West of the country with small amplitude in the diurnal cycle there. On average, the peak in precipitation amount leads the peak in frequencies of precipitation by 30 min to 1 h. Together with a high resolution climatological summer rain rate presented here and a detailed table for all stations, this study is a benchmark upon which model output or satellite estimate of the diurnal cycle can be compared within the region. Copyright © 2012 Royal Meteorological Society